2018
DOI: 10.1038/s41598-018-33016-7
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a novel antimicrobial peptide against Pseudomonas aeruginosa biofilms

Abstract: With the increasing recognition of biofilms in human disease, the development of novel antimicrobial therapies is of critical importance. For example, in patients with cystic fibrosis (CF), the acquisition of host-adapted, chronic Pseudomonas aeruginosa infection is associated with a decline in lung function and increased mortality. Our objective was to test the in vitro efficacy of a membrane-active antimicrobial peptide we designed, termed 6K-F17 (sequence: KKKKKK-AAFAAWAAFAA-NH2), against multidrug resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 63 publications
5
30
0
Order By: Relevance
“…The intermetallic distance of 14.4 A is rather smaller than that observed in the related structure 6e corresponding to a more compact concertina fold. As expected, the circumference is slightly larger, with distances between 'apex' O atoms [O (11), O (14) and O (17)] falling into a narrow range (9.9-10.1 A). These three atoms form an approximate equilateral triangle, indicating high symmetry of the system.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The intermetallic distance of 14.4 A is rather smaller than that observed in the related structure 6e corresponding to a more compact concertina fold. As expected, the circumference is slightly larger, with distances between 'apex' O atoms [O (11), O (14) and O (17)] falling into a narrow range (9.9-10.1 A). These three atoms form an approximate equilateral triangle, indicating high symmetry of the system.…”
Section: Resultssupporting
confidence: 70%
“…7,8 Alternatively, CAMPs may cross the membrane barrier and interact with intracellular targets with lethal consequences [9][10][11] or indeed have combinations of modes of action. 4,12 CAMPs and derivatives have been investigated as clinical antibiotics, [13][14][15] but unfortunately their pharmacokinetic proles tend to be unfavourable and large scale manufacture presents a challenge. 16 Nevertheless it is worth noting that a number of CAMPs are currently under commercial development, with attempts being made to enhance the properties of natural systems using strategies such as peptide stapling 17 to improve structural integrity and enzymatic stability.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is necessary to use antimicrobial agents, that besides being not toxic for the patients, are capable to deeply penetrate into dentinal system, and, in turn, efficiently eliminate bacteria, possibly even when structured in biofilm. Notoriously, once structured as biofilm, microbial agents have enhanced resistance to antibiotics and disinfectants, given their complex and heterogeneous arrangement as a microbial sessile population embedded into an extracellular, minimally permeable polymeric matrix [18][19][20] . Among the numerous soluble factors involved in biofilm formation/maturation, quorum sensing molecule, including pyoverdine 21,22) and eDNA 23,24) , have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Further, 6K-F17 is highly effective in disrupting and killing pre-formed multidrug resistant P. aeruginosa biofilms [32]. The co-treatment with tobramycin demonstrated that 6K-F17 could potentiate tobramycin bacterial killing activity at low doses by helping to eliminate pre-formed biofilms [32].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed the ability of the non-amphipathic antimicrobial peptide 6K-F17 to inhibit the growth of clinical multidrug resistant P. aeruginosa strains that were isolated from chronically infected CF patients [31]. Further, 6K-F17 is highly effective in disrupting and killing pre-formed multidrug resistant P. aeruginosa biofilms [32]. The co-treatment with tobramycin demonstrated that 6K-F17 could potentiate tobramycin bacterial killing activity at low doses by helping to eliminate pre-formed biofilms [32].…”
Section: Introductionmentioning
confidence: 99%